An Overview of Multimodal Neuroimaging Using Nanoprobes - Sridhar, Sriram (2018)
Nanomaterials have gained tremendous significance as contrast agents for both anatomical and functional preclinical bio-imaging. Contrary to conventional medical practices, molecular imaging plays an important role in exploring the affected cells, thus providing precision medical solutions. It has been observed that incorporating nanoprobes improves the overall efficacy of the diagnosis and treatment processes. These nano-agents and tracers are therefore often incorporated into preclinical therapeutic and diagnostic applications. Multimodal imaging approaches are well equipped with nanoprobes to explore neurological disorders, as they can display more than one type of characteristic in molecular imaging. Multimodal imaging systems are explored by researchers as they can provide both anatomical and functional details of tumors and affected tissues. In this review, we present the state-of-the-art research concerning multimodal imaging systems and nanoprobes for neuroimaging applications.